Circumstances and toxicology of violence-related deaths among young people who have had contact with the youth justice system: a data linkage study - Melissa Willoughby; Jesse T. Young; Katie Hail-Jares; Matthew J. Spittal; Rohan Borschmann; George Patton; Susan M. Sawyer; Emilia Janca; Linda Teplin; Ed Heffernan; Stuart A. Kinner (BMC, 2021)
Abstract Background Young people who have had contact with the youth justice system have an increased risk of dying from violence. Examining the context of violence-related deaths is essential in informing prevention strategies. We examined the circumstances and toxicology of violence-related deaths among young people who have had contact with the youth justice system in Queensland, Australia. Methods This data linkage study linked youth justice records from Queensland, Australia (30 June 1993-1 July 2014) on 48,670 young people to national death and coroner records (1 July 2000-1 January 2017). Circumstances and toxicology of deaths were coded from coroner's records. We calculated the incidence of violence-related deaths that were reported to a coroner. Fisher's exact tests were used to examine crude differences in the circumstances and toxicology of violence-related death, according to sex and Indigenous status. Results There were 982 deaths reported to a coroner in the cohort. Of which, 36 (4%) were from violence-related causes (incidence: 6 per 100,000 person-years, 95% confidence interval: 4-8). People who died from violence were most frequently male (n = 28/36; 78%), and almost half were Indigenous (n = 16/36; 44%). The majority of violence-related deaths involved a weapon (n = 24/36; 67%), most commonly a knife (n = 17/36; 47%). Compared to men where the violent incident was most frequently preceded by an altercation (n = 12/28; 43%), for women it was frequently preceded by a relationship breakdown or argument (n < 5; p = 0.004). Substances most commonly present in toxicology reports were cannabis (n = 16/23; 70%) and alcohol (n = 15/23; 65%). Conclusions Therapeutic alcohol and other drug programs, both in the community and detention, are likely important for reducing violence-related deaths among young people who have had contact with the youth justice system. The majority of violence-related deaths among women were in the context of intimate partner violence, indicating the urgent need for interventions that prevent intimate partner violence in this population. Diversion programs and increased investment in health and social services may reduce the overrepresentation of Indigenous people in the youth justice system and in violence-related deaths.